Pendidikan Kesehatan Tentang Pencegahan Scabies pada Santri di Pondok Pesantren Modern Al-Hidayah Kota Jambi - Hasyim Kadri; Salvita Fitrianti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
A high prevalence of scabies is generally found in environments with high density of residents and interpersonal contacts such as Islamic boarding schools, prisons and orphanages. The impact arising from scabies caused by personal hygiene problems includes the frequency of bathing, washing hands, using soap or not, changing clothes and towels, clean bedding, hair hygiene, nail hygiene, dental and oral hygiene, foot and shoe care, eye hygiene, ear hygiene and nose hygiene. The clinical manifestations that are usually caused are itching which is usually severe and will get worse at night and there are blisters or small, thin bumps on the skin.The solution of this community service is to provide health education and scabies prevention simulations to change or increase students' knowledge about scabies prevention.The results obtained by the participants in following the activities of community service well all followed the activity sequence without leaving the venue, a total of 37 participants were santri wati, they enthusiastically asked questions and participated in practicing the activities taught and carried out simulations of prevention of scabies.